AN APPRAISAL OF THE REFERENCE RANGE FOR BLEEDING TIME AMONGST YOUNG NIGERIA ADULTS - Uroko, Favour C.; Obasi, Blessing Ihemelandu (Student’s Journal of Health Research Africa, 2025)
Background This study aims to create baseline values that reflect the distinct physiological traits of this population by evaluating the reference range for bleeding time among young adults in Nigeria. Bleeding time, an important hemostatic characteristic, varies among groups as a result of genetic, environmental, and lifestyle influences. This study seeks to add useful information to the sparse body of knowledge on hemostatic characteristics particular to the Nigerian population by undertaking a thorough examination of bleeding time in a sample of young Nigerian people. Method With a cross-sectional design, the study enrolls a varied group of healthy adults between the ages of 18 and 30. Bleeding time measurements are made using standardized procedures, and the outcomes are contrasted with accepted global reference ranges, gender, platelet count, and bleeding time variability. Results This study adds to our understanding of hemostasis in various groups and emphasizes the value of individualized reference intervals for diagnostic and therapeutic procedures. Conclusion The researcher’s conclusions have significance for clinical practice, assisting medical personnel in accurately diagnosing bleeding problems and enhancing patient treatment plans for young adults in Nigeria. Recommendations Healthcare institutions and diagnostic laboratories in Nigeria should adopt bleeding time reference ranges that reflect the local population’s physiological characteristics rather than relying solely on international standards.